2005
DOI: 10.1590/s0100-879x2005000900017
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical cord blood and neonatal endothelin-1 levels in preterm newborns with and without respiratory distress syndrome

Abstract: Increased pulmonary vascular resistance in preterm newborn infants with respiratory distress syndrome is suggested, and endothelin-1 plays an important role in pulmonary vascular reactivity in newborns. We determined umbilical cord blood and neonatal (second sample) levels of endothelin-1 in 18 preterm newborns with respiratory distress syndrome who had no clinical or echocardiographic diagnosis of pulmonary hypertension and 22 without respiratory distress syndrome (gestational ages: 31.4 ± 1.6 and 29.3 ± 2.3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…27 Higher ET-1 in preterm infants who later developed BPD suggests the early involvement of pulmonary hypertension in the pathogenesis of BPD. 28,29 ET-1 is able to augment the production of oxygen radicals from alveolar macrophages, which subsequently increases alveolar inflammation with a positive feed back to up-regulate ET-1 production until eventually BPD ensues. 30 Early ET-1 assay can estimate the severity of pulmonary vascular hypertension and respiratory inflammation; both components are essential for the development of BPD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Higher ET-1 in preterm infants who later developed BPD suggests the early involvement of pulmonary hypertension in the pathogenesis of BPD. 28,29 ET-1 is able to augment the production of oxygen radicals from alveolar macrophages, which subsequently increases alveolar inflammation with a positive feed back to up-regulate ET-1 production until eventually BPD ensues. 30 Early ET-1 assay can estimate the severity of pulmonary vascular hypertension and respiratory inflammation; both components are essential for the development of BPD.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, when blood samples were obtained 18 to 40 hours after birth, ET-1 concentrations correlated with duration of mechanical ventilation. 28 However, it was hard to interpret whether ET-1 was a marker for the severity of the initial illness that could successfully predict the duration of ventilation or it was released as a result of the pulmonary damage caused by mechanical ventilation. Finally, the expression of ET-1in the immediate postnatal age may reflect the stress experienced by these infants during birth.…”
Section: Discussionmentioning
confidence: 99%
“… 28 and Benjamin et al . 29 showed that endothelin -1 level was increased in newborns with respiratory distress syndrome. Mei Mei et al .…”
Section: Discussionmentioning
confidence: 99%
“…Like our study, Kojima et al [19] found out that plasma ET-1 concentrations in newborns with RDS were higher compared to the newborns with RDS-2. A study of Benjamin et al [20] demonstrated that infants with and without RDS had similar umbilical cord ET-1 concentrations, whereas ET-1 concentrations were higher in RDS than in control newborns 18–40 hours after birth. The increased vascular resistance in RDS may be related to high plasma ET-1 concentrations.…”
Section: Discussionmentioning
confidence: 99%